Cold Therapy pada Luka Operasi Ortopedi - Nugraheni, Auliya Tunnisaa; Masfuri, Masfuri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of the cooling method on overcoming acute responses such as pain after surgery. It has three main effects: reducing pain (analgesia), anti-inflammatory effects, and edema/swelling. The method used was a systematic search for articles with a randomized controlled trial (RCT) research design through the PubMed, ProQuest, ScienceDirect, and ClinicalKey databases from October 2013 to October 2023 using the keywords